Preparing accountants of the future: A programme in accounting data and analytics - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2021)
The accounting profession is rapidly evolving due to technological innovations. Technologies such as the Internet of things, smart sensors, cloud computing, robotics, and artificial intelligence are combining to disrupt the way that businesses operate. It is predicted that, over the next decade, information technology (IT) will significantly transform the accounting profession.